A determinant model for Islamic management / Azman Che Omar - Che Omar, Azman (2015)
The discussion of Islamic management is not a new phenomenon in today's academia. However, through the perusal of review of literature had shown that there is no such an empirical research being done yet on factors that cause the practice of Islamic management in any organization, either Islamic organization or modern organization. For every Muslim manager, it is the amanah, or entrusted responsibility to practice the Islamic management in his or her operation of the organization. The goal of today's contemporary management is ensuring the organization to implement the right management in achieving its objectives. However, for Islamic organizations, the managers must set the objectives and implement the strategies that are consistent with the shariah teachings. the Muslim managers must ensure that functions and activities of management are following the shariah regulations for meeting the intended al-falah. The aim of the paper is to find out the determinant factors that may influence the practice of the Islamic management. In ensuring that the relevant factors are rightly identified, the right determinant model for Islamic management is proposed and developed. The main factors that influences the practice of the Islamic management are the religiosity of the Muslim managers, the Islamic leadership of the boss and the role of Muslim employees. The proposed model is further discussed to make them workable and having the construct validity. The analysis of the model is administered through SPSS and SEM with AMOS. The outcome of the model is the Islamic management index that can become the religious benchmark for identifying the implementation of Islamic management in any Islamic organization.